The Bom Santo Cave (Lisbon, Portugal): catchment, diet, and patterns of mobility of a Middle Neolithic population - Carvalho, António Faustino (2017)
The study of the Bom Santo Cave (central Portugal), a Neolithic cemetery, indicates a complex social, palaeoeconomic, and population scenario. With isotope, aDNA, and provenance, analyses of raw materials coupled with stylistic variability of material culture items and palaeogeographical data, light is shed on the territory and social organization of a population dated to 3800-3400 cal BC, i.e. the Middle Neolithic. Results indicate an itinerant farming, segmentary society, where exogamic practices were the norm. Its lifeway may be that of the earliest megalithic builders of the region, but further research is needed to correctly evaluate the degree of this community's participation in such a phenomenon.